2021
DOI: 10.1136/jech-2020-215039
|View full text |Cite
|
Sign up to set email alerts
|

Is area deprivation associated with greater impacts of COVID-19 in care homes across England? A preliminary analysis of COVID-19 outbreaks and deaths

Abstract: IntroductionThe COVID-19 pandemic has disproportionately impacted care homes and vulnerable populations, exacerbating existing health inequalities. However, the role of area deprivation in shaping the impacts of COVID-19 in care homes is poorly understood. We examine whether area deprivation is linked to higher rates of COVID-19 outbreaks and deaths among care home residents across upper tier local authorities in England (n=149).MethodsWe constructed a novel dataset from publicly available data. Using negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 2 publications
0
17
0
Order By: Relevance
“…Studies that have associated COVID-19 cases and deaths with area deprivation highlighted occupational exposure, overcrowding, public transport use and underlying health conditions as mechanisms, which may also explain the unequal increases in psychological distress found here. 39 Since lockdown measures prevented young adults from leaving their residential area, the conditions found in the most deprived areas may have had a stronger influence on those previously able to access less deprived areas in their everyday activities. 40 Supporting the role of the economic consequences of the pandemic in mental health, we found that losing one's job or work hours was related to increased psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that have associated COVID-19 cases and deaths with area deprivation highlighted occupational exposure, overcrowding, public transport use and underlying health conditions as mechanisms, which may also explain the unequal increases in psychological distress found here. 39 Since lockdown measures prevented young adults from leaving their residential area, the conditions found in the most deprived areas may have had a stronger influence on those previously able to access less deprived areas in their everyday activities. 40 Supporting the role of the economic consequences of the pandemic in mental health, we found that losing one's job or work hours was related to increased psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…This difference may be due to poorer underlying health among care home residents in more deprived areas. 163,164…”
Section: Covid-19 Impactsmentioning
confidence: 99%
“…The high importance of these features reflects the sad fact that this particularly vulnerable group is difficult to protect [50] (for an international review about protection measures see [51]), despite commonly applied, but also highly criticized isolation measures [52,53]. In addition, there was evidence that COVID-19 outbreaks in nursing homes were associated with spatial deprivation and that the latter was a major risk factor for COVID-19 deaths in nursing home residents [54].…”
Section: Nursing Home Population and Healthmentioning
confidence: 99%